Anticancer and Reversing Multidrug Resistance Activities of Natural Isoquinoline Alkaloids and their Structure-activity Relationship - Qing, Zhi-Xing; Huang, Jia-Lu; Yang, Xue-Yi; Liu, Jing-Hong; Cao, Hua-Liang; Xiang, Feng; Cheng, Pi; Zeng, Jian-Guo (Current Medicinal Chemistry, 2018)
The severe anticancer situation as well as the emergence of multidrug-resistant (MDR) cancer cells has created an urgent need for the development of novel anticancer drugs with different mechanisms of action. A large number of natural alkaloids, such as paclitaxel, vinblastine and camptothecin have already been successfully developed into chemotherapy agents. Following the success of these natural products, in this review, twenty-six types of isoquinoline alkaloids (a total of 379 alkaloids), including benzyltetrahydroisoquinoline, aporphine, oxoaporphine, isooxoaporphine, dimeric aporphine, bisbenzylisoquinoline, tetrahydroprotoberberine, protoberberine, protopine, dihydrobenzophenanthridine, benzophenanthridine, benzophenanthridine dimer, ipecac, simple isoquinoline, pavine, montanine, erythrina, chelidonine, tropoloisoquinoline, azafluoranthene, phthalideisoquinoline, naphthylisoquinoline, lycorine, crinane, narciclasine, and phenanthridone, were summarized based on their cytotoxic and MDR reversing activities against various cancer cells. Additionally, the structure-activity relationships of different types of isoquinoline alkaloid were also discussed. Interestingly, some aporphine, oxoaporphine, isooxoaporphine, bisbenzylisoquinoline, and protoberberine alkaloids display more potent anticancer activities or anti-MDR effects than positive control against the tested cancer cells and are regarded as attractive targets for discovery new anticancer drugs or lead compounds.
Keywords: oxoaporphine